Activity of intestinal efflux pumps in M-406 mammary adenocarcinoma bearing mice with metabolic syndrome treated with cyclophosphamide metronomic chemotherapy - Barranco, Maria Manuela (2019)
High fat diet (HFD) cause obesity and MS, which are associated with breast cancer progression. MC (chronic, low dose, with no extended rest periods, drug administration) is a promising treatment strategy with low toxicity. Some chemotherapeutic drugs are substrates of multidrug resistance-associated protein 2 (Mrp2) and Pglycoprotein (P-gp), efflux pumps that limit the intestinal absorption and are modified by alterations produced in MS. We previously demonstrated the induction of MS in CBi male mice. The aim was to assess the alteration produced by MS in Mrp2 and P-gp activity as intestinal biochemistry barrier and its influence on the therapeutic effect of Cy MC. CBi male mice (5 weeks n= 20/group), were fed with a chow diet (C) and a diet with 40 % calories of fat (HFD) throughout the experiment. At 16 weeks, the development of MS was confirmed by biochemical and morphological parameters. The activity of Mrp2 and P-gp was evaluated using the in vitro model of everted intestinal sacs. Once the MS features were settled, mice were challenged s.c. with M-406 (day 0); when the tumor was palpable, mice were distributed into 4 groups (n= 8/group): GI: C no treatment, GII:C+Cy (30 mg/kg/day in drinking water), GIII: HFD no treatment and GIV: HFD+Cy. Efflux of Mrp2 substrate DNP-SG decreased 64% in HFD respect to C (p<0.05); transport rate of rhodamine 123 by P-gp decreased 55 % in HFD vs. C (p<0.05). At the end of the experiment (day 22), the tumor volume was lower in GII vs GI and in GIV vs GIII (p<0.0001).The % inhibition of tumor growth in GII was greater than that of GIV (p= 0.0524). It was observed a 30% decrease in body weight in GIV, indicating toxicity. We conclude that the induction of MS impairs the intestinal activity of Mrp2 and P-gp and these modifications may produce a change in Cy absorption, leading to toxicity along with therapeutic effect; also, MC has lower antitumor effectiveness in animals with MS so that the drug schedule should be re-designed.